Experimental diagnostics on potential degradation of a selected building construction - Eštoková Adriana; Hološová Miriama; Terpáková Eva (Selected Scientific Papers: Journal of Civil Engineering, 2020)
The aim of the study was to evaluate the historical building of the Old Town Hall of Košice city in terms of degradation processes of building materials. Regular maintenance, especially of historic buildings, is essential in terms of preserving the historic architectural heritage. Research was focused on selected parts of the basement of the historical construction with a special regard to the effect of humidity, salinity and carbonation of masonry structures. Samples were collected in the building basement and subsequently analysed in the laboratory. Chemical analysis of materials was performed by X–ray fluorescence analysis and the soluble salts were investigated by colorimetry. In addition, the content of sulphates was confirmed by infrared spectroscopy. Humidity of individual samples ranged from very low to very high, the highest values were measured around the perimeter of the room (positioning to the outside terrain). The carbonation ranged from grade III to IV, sulphates were detected in practically all samples. The results of study can help to design corrective measures.